Pengaruh Profitabilitas, Keputusan Investasi Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Ranti Salmawati; Rita Tri Yusnita; Kusuma Agdhi Rahwana (CV. ULIL ALBAB CORP, 2023)
Firm value is a description of the company's performance in reflecting the prosperity of its shareholders. Maximizing the value of the company is the main goal of the company, because maximizing the value of the company also means maximizing the prosperity of shareholders. This study aims to determine the effect simultaneously and partially on Profitability as measured by Return on Assets (ROA), Investment Decisions as measured by Price Earning Ratio (PER) and Dividend Policy as measured by the Dividend Payout Ratio (DPR) on Company Value as measured by Price Book Value (PBV). The population used in this study are banking companies listed on the Indonesian Stock Exchange (IDX) for the 2021 period. The method used in this research is a quantitative method with the type of associative descriptive analysis research. The sample selection used purposive sampling method. The sample used was 15 banking companies listed on the Indonesian Stock Exchange (IDX) for the 2021 period. The data source in this study was secondary data in the form of audited financial reports obtained from www.idx.co.id. The data analysis technique used is multiple linear regression with the help of SPSS 25. Based on the results of the study it was concluded that profitability, investment decisions and dividend policies simultaneously have no significant effect on firm value. Partially Profitability has a significant effect on firm value. Meanwhile, investment decisions and dividend policies partially have no significant effect on firm value.